Evaluation of LiDAR Point Clouds Density in the Interpolation of Digital Terrain Models for Power Line Planning in Northeast Brazil - Pacheco, Admilson da Penha; Centeno, Jorge Antonio Silva; Silva, Claudionor Ribeiro (Anuário do Instituto de Geociências, 2022)
Mapping activities for the implementation of basic and executive projects for electric power transmission lines systematically involves topographic surveys. This study presents the results of a comparative study on the influence of the density of aerial survey points, LiDAR (Light Detection and Ranging), for the calculation of digital terrain models (DTMs) in typical areas of the northeastern region of Brazil, in the context of modeling ground for planning electricity transmission lines. The study area is the region covered by the 230 kV Ibicoara/Brumado transmission line, located in the state of Bahia/Brazil.. In part of this region, elevations of the mountains of the Western Edge of Chapada Diamantina predominate. Therefore, points with varying densities were used to interpolate DTMs in different environments. Point cloud classification (Airborne LiDAR) was performed using the TerraScan program using semi-automatic classification methods, followed by manual refinements. To evaluate the terrain models obtained with different point densities, four areas were selected under transmission line: Area 1 (24.4/m2), Area 2 (46.0/m2), Area 3 (33.7/m2) e Area 4 (29.7/m2). The Airborne LiDAR survey was performed with an Optech ALTM Pegasus HD500 sensor, calibrated to obtain a density of 15 points/m2. The results showed that, depending on the nature of the vegetation cover, less dense laser surveys do not offer enough quality to generate DTMs. However, in some cases, when the vegetation is denser and the terrain is not flat, the quality of the DTM decreases as the density of the points decreases. The study shows that the survey density must be suitable for the region to be analyzed. An important guideline would be to repeat this study in other areas with different coverage and relief variations, in order to create specifications to serve as a basis for planning LiDAR surveys on other transmission lines.